The effects of antioxidant supplementation on soccer performance and recovery: A critical review of the available evidence - Poulios, A.; Papanikolaou, K.; Draganidis, D.; Tsimeas, P.; Chatzinikolaou, A.; Tsiokanos, A.; Jamurtas, A. Z.; Fatouros, I. G. (Nutrients, 2024)
Background Soccer is linked to an acute inflammatory response and the release of reactive oxygen species (ROS). Antioxidant supplements have shown promising effects in reducing muscle damage and oxidative stress and enhancing the recovery process after eccentric exercise. This critical review highlights the influence of antioxidant supplements on performance and recovery following soccer-related activity, training, or competition.